Estrous cycle state-dependent renewal of appetitive behavior recruits unique patterns of Arc mRNA in female rats - Hilz, Emily N.; Agee, Laura A.; Jun, Donyun; Monfils, Marie-H.; Lee, Hongjoo J. (Frontiers in Behavioral Neuroscience, 2023)
Renewal is a behavioral phenomenon wherein extinction learning fails to generalize between different contextual environments, thereby representing a significant challenge to extinction-based rehabilitative therapies. Previously, we have shown that renewal of extinguished appetitive behavior differs across the estrous cycle of the female rat. In this experiment that effect is replicated and extended upon to understand how the estrous cycle may modulate contextual representation at the neuronal population level to drive renewal. Estrous cycle stage (i.e., proestrus (P, high hormone) or metestrus/diestrus (M/D, low hormone)) was considered during two important learning and behavioral expression windows: at extinction training and during long-term memory (LTM)/renewal testing. Rats in P during context-dependent extinction training but in a different stage of the estrous cycle during LTM and renewal testing (P-different) were shown to exhibit more renewal of conditioned foodcup (but not conditioned orienting) behavior compared to rats in other estrous cycle groups. Importantly, we discovered this depends on the order of tests. Cellular compartment analysis of temporal activity using fluorescence in situ hybridization (catFISH) for Arc mRNA was conducted after the distinct context-stimulus exposures. P-different rats showed differential Arc mRNA expression in regions of the prefrontal cortex (PFC), amygdala, and hippocampus (HPC). For each case P-different rats had more co-expression (i.e., expression of both nuclear and cytoplasmic) of Arc mRNA compared to other groups; specific to the dorsal HPC, P-different rats also had a more robust Arc mRNA response to the extinction context exposure. These data suggest female rats show state-dependent renewal of appetitive behavior, and differences in context and conditioned stimulus representation may drive this effect.